2015
DOI: 10.1021/acs.jpcc.5b03830
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Solvation-Controlled Reactions in Stimuli-Responsive Nanoreactors

Abstract: Metallic nanoparticles embedded in stimuli-responsive polymers can be regarded as nanoreactors since their catalytic activity can be changed within wide limits: the physicochemical properties of the polymer network can be tuned and switched by external parameters, e.g. temperature or pH, and thus allows a selective control of reactant mobility and concentration close to the reaction site. Based on a combination of Debye's model of diffusion through an energy landscape and a two-state model for the polymer, her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(101 citation statements)
references
References 55 publications
2
99
0
Order By: Relevance
“…The re-partitioning and enrichment of MO at the hydrogel/solvent interface, in turn, would lead to a reduced MO concentration adjacent to the nanoparticle. According to our theory 24 this depletion of reactants should effectively reduce the rate. Secondly, from the UV-vis spectra (see Figure s10), we found that the core-shell particles can absorb more light at 15 °C than at 40 °C, thereby signifying that the core-shell particles can produce more active OH radicals at the nanocube at the lower temperature.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The re-partitioning and enrichment of MO at the hydrogel/solvent interface, in turn, would lead to a reduced MO concentration adjacent to the nanoparticle. According to our theory 24 this depletion of reactants should effectively reduce the rate. Secondly, from the UV-vis spectra (see Figure s10), we found that the core-shell particles can absorb more light at 15 °C than at 40 °C, thereby signifying that the core-shell particles can produce more active OH radicals at the nanocube at the lower temperature.…”
Section: Resultsmentioning
confidence: 92%
“…As we find that the reaction is fully surfacecontrolled (i.e., the reactant diffusive transport is much faster than the surface reaction, see supporting information), MO enrichment at the nanocube surface would lead proportionally to a higher surface rate. 24 However, details on such a rate enhancement depend on the exact spatial partitioning of the MO molecules in the nanoreactor that is experimentally not easily accessible. Another reason for the enhanced rate is related to the stronger absorption of light and narrower band gap in case of the core-shell particles (see Figure s9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in realistic systems the mobility will be certainly slowed down to some extent but not vanish. ∆G may be even negative (attractive) if the reactant interacts favorably with the polymer as found for rather hydrophobic reactants and collapsed PNIPAM-based hydrogels [11,12]. Since ∆G enters Eq.…”
Section: A Optimizing the Number Of Nanocatalystsmentioning
confidence: 97%
“…This theory is based on the well-known seminal paper by Debye [13] and considers a single nanoparticle located in the center of a hollow thermosensitive network [12]. Here, the substrate that reacts at the surface of the nanoparticle diffuses through a free-energy landscape created by the hydrogel environment.…”
Section: Introductionmentioning
confidence: 99%